Embryonic manipulations shape life-long, heritable stress responses through complex epigenetic mechanisms: a review - Kisliouk, Tatiana; Ravi, Padma Malini; Rosenberg, Tali; Meiri, Noam (Frontiers in Neuroscience, 2024)
Enhancing an organism's likelihood of survival hinges on fostering a balanced and adaptable development of robust stress response systems. This critical process is significantly influenced by the embryonic environment, which plays a pivotal role in shaping neural circuits that define the stress response set-point.While certain embryonic conditions offer advantageous outcomes, others can lead to maladaptive responses. The establishment of this response set-point during embryonic development can exert lifelong and inheritable effects on an organism's physiology and behavior. This review highlights the significance of multilevel epigenetic regulation and the intricate cross-talk among these layers in response to heat stress during the embryonic period, with a particular focus on insights gained from the avian model.